Knowledge, Perceptions, Awareness, and Incidence of Cognitive Health Issues among Undergraduates at Risk for Polycystic Ovarian Disease (PCOD) - Dr. Shweta Sehgal; Aalia Khan; Naisha Behal (International Journal of Medical Science and Clinical Research Studies, 2025)
INTRODUCTION: Polycystic ovarian disorder is the most common endocrine disorder seen in women of reproductive age. Since emotions are largely influenced by hormonal activity, this imbalance in hormone levels can significantly impact mental health. Young women with PCOD can have body image and self-esteem issues due to difficulty in losing weight and excess facial hair growth. Not only that but irregular menstrual cycles and fertility changes can cause them to have chronic high stress levels and anxiety. MATERIAL & METHOD: An online structured questionnaire was created to collect data from 123 medical UG students of batch 2023 of various medical colleges. RESULTS: Most participants began menstruating between ages 12 and 14, with a majority tracking their menstrual cycles and being informed about PCOD. While 90% of participants experience dysmenorrhea, only a small proportion take medication regularly for it. The majority sleep 6-8 hours daily, though some report irregular or insufficient sleep, indicating a need for better sleep hygiene. Stress levels are moderate for most, with a significant number experiencing anxiety, particularly related to academic pressures. Dietary habits show a reliance on fast food, with 52% consuming it 2-4 times weekly, which may contribute to weight management difficulties for some participants. CONCLUSION: These findings suggest the importance of targeted interventions, including stress management, improved sleep hygiene, and healthier eating habits, to enhance the overall well-being and quality of life for young women, particularly concerning reproductive health and academic pressures.